2012
DOI: 10.1016/j.jacc.2012.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Midwall Fibrosis as a Predictor of Mortality and Morbidity After Cardiac Resynchronization Therapy in Patients With Nonischemic Cardiomyopathy

Abstract: Midwall fibrosis is an independent predictor of mortality and morbidity in patients with DCM undergoing CRT. The outcome of DCM with midwall fibrosis is similar to that of ICM. This relationship is mediated by both pump failure and sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
3
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 34 publications
(31 reference statements)
3
107
3
5
Order By: Relevance
“…The majority of studies evaluated the presence or absence of LGE by visual analysis. 4,6,7,10,[13][14][15][16][17][18][19][20]22,[24][25][26][27][28][29]30,32 Duration of follow-up ranged from 1 year to 5.3 years; mean follow up was 3 years. The majority of reports considered a composite arrhythmic end-point formed by sudden cardiac death and/or aborted cardiac arrest, sustained ventricular arrhythmias and/or appropriate ICD therapies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies evaluated the presence or absence of LGE by visual analysis. 4,6,7,10,[13][14][15][16][17][18][19][20]22,[24][25][26][27][28][29]30,32 Duration of follow-up ranged from 1 year to 5.3 years; mean follow up was 3 years. The majority of reports considered a composite arrhythmic end-point formed by sudden cardiac death and/or aborted cardiac arrest, sustained ventricular arrhythmias and/or appropriate ICD therapies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The majority of reports considered a composite arrhythmic end-point formed by sudden cardiac death and/or aborted cardiac arrest, sustained ventricular arrhythmias and/or appropriate ICD therapies. 4,5,7,8,10,13,14,[16][17][18]20,22,25,[28][29][30][31] In two reports history of arrhythmic events was the end-point analyzed. 9,32 These data were not used to calculate annual event rates, but were included in the evaluation of pooled OR.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…(57,58) Published data revealed a discrepancy between clinical and echocardiographic responses, with more studies reporting clinical response than echocardiographic improvement. (59) Reduced response to CRT has been associated with a high myocardial scar burden, (60) posterolateral (61) and mid-wall (62) scar location, extreme mechanical dyssynchrony, (63) severe right ventricular dysfunction, pulmonary hypertension, end-stage renal failure, and valvular heart disease. On the other hand, better CRT outcomes have been reported in female patients (64,65) and those with non-ischaemic cardiomyopathy.…”
Section: Cardiac Resynchronisation Therapymentioning
confidence: 99%
“…On the other hand, better CRT outcomes have been reported in female patients (64,65) and those with non-ischaemic cardiomyopathy. (62) Efforts have been made to identify factors which may better predict response to CRT. The Predictors of Response to CRT trial (66) and EchoCRT study (54) revealed that echocardiographic measures of mechanical dyssynchrony did not reliably predict CRT response.…”
Section: Cardiac Resynchronisation Therapymentioning
confidence: 99%
“…In order to achieve a better selection, the existence of factors, which could predict the response to CRT has been extensively investigated [32][33][34][35]. Factors, like female gender [36][37][38] and non-ischemic etiology [38,39] are related to a positive response to CRT and, on the contrary, some comorbidities, like end-stage renal failure and pulmonary hypertension appear to diminish the response to CRT [38]. Also, QRS duration and LBBB correlate positively with CRT response [40][41][42].…”
Section: Imaging Predictive Factorsmentioning
confidence: 99%